Pajak Penghasilan (PPh) Notaris Dalam Akta Jual-Beli Tanah Dan Bangunan (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2025)
Taxes are one of the main sources of state revenue that is coercive, including in land and building sales transactions. In this process, notaries have an important role to ensure that tax obligations, such as Income Tax (PPh) and Land and Building Rights Acquisition Duty (BPHTB), are fulfilled before the ratification of the deed. Validation of proof of tax payment by a notary/PPAT aims to ensure the legality and reasonableness of the transaction. This article discusses the role of notaries in taxation, tax validation, and the challenges faced in its implementation.